Mothers’ Views About Lumbar Puncture for Their Children in a Maternity and Children’s Hospital in Najran, Saudi Arabia - Alshaibari KS; Hasan ER; Dammaj MZ; Sharaf Adeen IA (Dove Medical Press, 2021)
Khaled Sadeq Alshaibari,1 Eman Redhwan Hasan,2 Mayasa Zaid Dammaj,1 Iman Ali Sharaf Adeen3 1Department of Pediatrics, College of Medicine, Najran University, Najran, Saudi Arabia; 2Emergency Department, Al-Zafer Hospital, Najran, Saudi Arabia; 3Pediatric Behavior and Development, King Fahad Medical City, Riyadh, Saudi ArabiaCorrespondence: Khaled Sadeq Alshaibari Email khalid22ye@gmail.comBackground: Refusal rates for offered pediatric lumbar puncture (LP) are high in many parts of the world, potentially hindering diagnosis and treatment for thousands of children. There is relatively little research about why such rates are so high. Understanding the formation and development of mothers’ opinions about LP could help identify barriers to accessing this modality to improve diagnostic and treatment outcomes in children with neurological and systemic diseases.Methods: We surveyed mothers of hospitalized children in the Maternity and Children’s Hospital in Najran in November and December 2018. We queried their familiarity with LP and their decision to accept or refuse LP when it was offered. The team recorded demographic data on survey respondents, as well as their stated reasons for their LP decisions, and used chi-square tests to evaluate the correlation between patient or parent characteristics and the decision to accept or refuse LP.Results: A total of 202 mothers responded to the survey, with a mean age of 30.7 (± 6.9); nearly all women were stay-at-home mothers (93.1%). Most (61.4%) lived in urban settings. Four in 10 respondents (40.6%) were not familiar with LP. A sizable minority of 89 mothers (44.0%) refused LP for their children when offered, most commonly citing fear of paralysis (39.3%) as the reason for refusal. Those who accepted LP were more likely to do so following physician advice than for any other reason (p < 0.001).Conclusion: Lumbar puncture refusal rates may be even higher than previously reported, and there is a pressing need to educate women on the diagnostic and therapeutic benefits of LP for their children. Maternal education from physicians may help improve acceptance rates for the procedure.Keywords: decision-making, maternal attitudes, pediatrics, survey data